Fish and seafood - Fernandes, Rhea. (Leatherhead [England] : Leatherhead Pub. ; Cambridge : Roya l Society of Chemistry, 2009)
"The Microbiology Handbook - Fish and Seafood is one in a series of Leatherhead Food International Microbiology Handbooks; others include D airy Products, and Meat Products. This book endeavours to provide the r eader with an easy-to-use reference to microorganisms in fish and seafo od." "The second edition of this handbook, in keeping with the previous edition, remains topical and features recent developments in fish and seafood processing that can influence the nature and scope of growth an d survival of microorganisms in these products, and hazards associated with them." "The new edition also incorporates the new Commission Regul ations on hygiene for foodstuffs and specific hygiene rules for food of animal origin, as well as microbiological criteria for foodstuffs; and new fish and shellfish toxins Lipophilic Shellfish Toxins, Azaspiracid s, Cyclic Imines, Gymnodimines, Spirolides, Pinnatoxins and Pteriatoxin s. This book remains a valuable source of information for microbiologis ts and food scientists responsible for food safety."--BOOK JACKET.
Includes bibliographical references and index.
Keywords: Fishes -- Microbiology -- Handbooks, manuals, etc; Fishery products -- Quality control -- Handbooks, manuals, etc